Information technology. International standardized profiles FVT2nn. Virtual terminal basic class. Register of control object type definitions. FVT222. Paged FEICO (Field Entry Instruction Control Object) No. 1 Part 9, (15th March 1995) - British Standards Institution,
No abstract available